Psychosocial and cultural perspectives on the war in Ukraine : imprints and dreamscapes - Šumylovyč, Bohdan; Żółkoś, Magdalena (2024)
This innovative and important book explores how war imprints on culture and the psychosocial effects of war on individuals and societies, based on the first few months after the outbreak of war in Ukraine in 2022